Corak Dan Warna Batik Penunjang Elemen Estetik Ruang Terbuka Hijau Di Kafe Pecah Kopi Bandung - Kudiya, Komarudin; Atik, Saftiyaningsih Ken (Waca Cipta Ruang, 2023)
Since 2010, the city of Bandung has undergone a strong growth spurt due to the expansion of cafes from the city center to the city's outskirts. The café is an alternate location for social contact among family members, friends, or professionals. To attract visitors, the cafe management must consider the ambient interior, which strives to provide visitor comfort by paying attention to lighting, interior design, music sound, and temperature as a preference for the purpose of selecting the cafe. The limitation of this research is that it is limited to green open spaces, whereas the goal is to find a correlation between batik patterns, which are used as supporting aesthetic elements, and the need for interior ambience that is unique, aesthetic, and provides a sense of comfort, which will have an impact on increasing visitor traffic or making them return the next time. The analytical descriptive and ethnographic methods were applied in this study. The findings of this study demonstrate that partnership between the batik showroom and the Pecah Kopi Bandung cafe can give benefits and value to both. This study's objective is to present real-world ideas and examples in the management of cafés that use green open spaces and can interact with managers in the arts and crafts industry to provide a sense of comfort and aesthetic value to their environment.